2013
DOI: 10.1371/journal.pone.0069201
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha rs1800629 Polymorphism and Risk of Cervical Lesions: A Meta-Analysis

Abstract: BackgroundTumor necrosis factor- alpha (TNF-α) is an inflammatory cytokine which may play important role on the immune response may control the progression of cervical lesions. There is a possible association between TNF-α rs1800629 G/A polymorphism and cervical lesions, but previous studies report conflicting results. We performed a meta-analysis to comprehensively assess the association between TNF-α rs1800629 polymorphism and cervical lesions risk.MethodsLiterature searches of Pubmed, Embase, Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…TNF-α is a highly pleiotropic cytokine with an important role in immune homeostasis, inflammation, and host defense (19). It is also involved in the defense against HPV infection by modifying viral replication (8), but unfortunately tumors can become TNF-α resistant. In fact, some malignant tumors are able to escape from TNF-α-induced cell death, suggesting that HPV-mediated TNF resistance is a key event in the multistep process leading to cervical cancer (19-20-21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α is a highly pleiotropic cytokine with an important role in immune homeostasis, inflammation, and host defense (19). It is also involved in the defense against HPV infection by modifying viral replication (8), but unfortunately tumors can become TNF-α resistant. In fact, some malignant tumors are able to escape from TNF-α-induced cell death, suggesting that HPV-mediated TNF resistance is a key event in the multistep process leading to cervical cancer (19-20-21).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factors alpha (TNF-α) and beta (TNF-β) play a central role in the adaptive immune response. They are mainly secreted by activated macrophages and are able to promote the host's defense mechanism by activating inflammatory processes (8). Although a moderate TNF level is necessary to maintain cell protected and prevent certain diseases through regulation of the immune response, excessive TNF secretion due to pathological conditions is associated with autoimmune diseases, infectious diseases and malignant tumors (9).…”
Section: Introductionmentioning
confidence: 99%
“…The two most commonly studied SNPs are in the promoter region of TNF , two G versus A transitions at positions −238 and −308; these have been shown to influence the expression of TNF-α [28,29]. A large number of studies have investigated the associations of TNF -238 G/A and/or −308G/A variants with cervical cancer risk, but results are contradictory [30,31]. Our data showed that −238 GG/GA and −308 AA genotypes in TNF were associated with increased cervical cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Common SNPs in the TNF-a promoter region have the ability to regulate the transcriptional activity. Such functional polymorphisms include TNF-a 308 and TNF-a -238G/A, and these have been associated with cervical cancer (Duarte et al, 2005;Li et al, 2013Li et al, , 2016Liu et al, 2012;Rotar et al, 2014).…”
Section: Tumor Necrosis Factor Alphamentioning
confidence: 99%